Protective effect of acute splenic irradiation in rats with traumatic brain injury. Issue 8 (15th April 2021) - Huang, Xiaofei; Lu, Yuanlan; Li, Lie; Sun, Tianjing; Jiang, Xuheng; Li, Mo; Zhang, Tianxi; Yu, Anyong
Abstract : Objective: To explore the protective effect of acute splenic irradiation against traumatic brain injury (TBI) in rats. Methods: A rat model of TBI was established according to Feeney's method. Splenic irradiation was performed by the reverse intensity-modulated radiation therapy (IMRT) source-axis distance (SAD) irradiation technique. Rat brain tissue samples were collected, the water content of the rat brain tissue was determined and the abundance of microglia was detected by immunofluorescence. Spleens were collected to measure the spleen index. Lung, liver, small intestine and kidney tissues were taken for hematoxylin and eosin staining to observe whether there was radiation-induced pathological damage. Peripheral blood was collected to detect tuftsin and the inflammatory factors IL-6 and IL-10. Results: Compared with the nonirradiated TBI rat group, the 4-h spleen irradiation TBI rat group showed (1) increased behavioral scores at 3 days after TBI ( P < 0.05), (2) reduced water content of the ipsilateral hemisphere at 3 days after TBI, (3) reduced spleen index at 3 and 7 days after TBI, (4) reduced number of microglia cells infiltrating around the lesion at 7 days after TBI, (5) reduced IL-6 levels at 3 days after TBI, (6) increased IL-10 levels at 3 and 5days after TBI and (7) Compared with the nonirradiated TBI rat group, the 8-h spleen irradiation TBI rat group showed reduced tuftsin levels at 3 and 7days after TBI. Conclusions: Acute splenic irradiation had a protective effect in rats with TBI.